Role of Sterylglucosidase 1 (Sgl1) on the pathogenicity of Cryptococcus neoformans: potential applications for vaccine development - Rella, Antonella; Mor, Visesato; Farnoud, Amir M.; Singh, Ashutosh; Shamseddine, Achraf A.; Ivanova, Elitza; Carpino, Nicholas; Montagna, Maria T.; Luberto, Chiara; Del Poeta, Maurizio (Frontiers in Microbiology, 2015)
Cryptococcosis caused by C. neoformans and C. gattii affects a large population and is a cause of significant morbidity and mortality. Despite its public health burden, there are currently no vaccines against cryptococcosis and new strategies against such infections are needed. In this study, we demonstrate that C. neoformans has the biochemical ability to metabolize sterylglucosides (SGs), a class of immunomodulatory glycolipids. Genetic manipulations that eliminate cryptococccal sterylglucosidase lead to the accumulation of SGs and generate a mutant strain (Δsgl1) that is avirulent in the mouse models of cryptococcosis. Interestingly, this mutant strain acts as a vaccine strain and protects mice against cryptococcosis following infection with C. neoformans or C. gattii. The immunity induced by the Δsgl1 strain is not CD4+ T-cells dependent. Immunocompromised mice, which lack CD4+ T-cells, are able to control the infection by Δsgl1 and acquire immunity against the challenge by wild-type C. neoformans following vaccination with the Δsgl1 strain. These findings are particularly important in the context of HIV/AIDS immune deficiency and suggest that the Δsgl1 strain might provide a potential vaccination strategy against cryptococcosis.